2016
DOI: 10.1002/chem.201603621
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships in Salinomycin: Cytotoxicity and Phenotype Selectivity of Semi‐synthetic Derivatives

Abstract: The ionophore salinomycin has attracted attention for its exceptional ability to selectively reduce the proportion of cells with stem-like properties in cancer cell populations of varying origin. Targeting the tumorigenicity of such cells is of interest as they are implicated in recurrence, metastasis, and drug resistance. Structural derivatives of salinomycin are thus sought after, both as tools for probing the molecular mechanism(s) underlying the observed phenotype effects, and for improving selectivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
(32 reference statements)
1
32
0
Order By: Relevance
“… 36 We recently demonstrated that salinomycin derivatives such as ethyl carbonate 3 with modifications to this position exhibit both increased basal toxicity and enhanced activity against breast cancer stem cells. 24 , 25 …”
Section: Resultsmentioning
confidence: 99%
“… 36 We recently demonstrated that salinomycin derivatives such as ethyl carbonate 3 with modifications to this position exhibit both increased basal toxicity and enhanced activity against breast cancer stem cells. 24 , 25 …”
Section: Resultsmentioning
confidence: 99%
“…However, a more systematic toxicology study may be required to examine the presence of delayed or latent toxicity to mammals. We also expect that toxicities could be alleviated by synthesizing less cytotoxic chemical derivatives, as tried in previous studies (42,43), or by conjugating the active compound to a delivery vehicle specific for virus-infected lung epithelial cells. Particularly, Brogström et al suggested that modifications to the C20 hydroxy group within the C-ring of salinomycin ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, Brogström et al suggested that modifications to the C20 hydroxy group within the C-ring of salinomycin ( Fig. 1A) would be beneficial in the context of selectivity (43). The combined therapeutic approach with salinomycin derivatives and a lower-dose NA inhibitor may also be valuable when the stockpiles of OSV-P are insufficient to respond to an influenza pandemic or when OSV-resistant viruses are circulating globally.…”
Section: Discussionmentioning
confidence: 99%
“…As polyether ionophores exhibit a broad spectrum of interesting pharmacological properties, at present, semi-synthetic derivatives of these natural products with improved activity profiles compared to those of the native structures are of top research interests. Although the site-specific modifications of ionophores are non-trivial with respect to their multifunctional nature and possible decomposition during synthesis, a few teams around the world have successfully followed synthetic approaches to generate LAS , MON , and SAL analogs; the modifications have been related mainly to the manipulations of either the C1 carboxyl of these biomolecules [ 6 , 15 , 16 , 17 , 18 , 19 , 20 ], or the C20 hydroxyl of SAL ( Figure 1 a) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Nevertheless, a definitely less explored direction of research is the synthesis as well as functional evaluation of the multivalent structures of polyether ionophores.…”
Section: Introductionmentioning
confidence: 99%